Enhancing Understanding of Moral Distress: The Measure of Moral Distress for Health Care Professionals - Epstein, Elizabeth G.; Whitehead, Phyllis B.; Prompahakul, Chuleeporn; Thacker, Leroy R.; Hamric, Ann B. (AJOB empirical bioethics, 2019)
Background: As ongoing research explores the impact of moral distress on health care professionals (HCPs) and organizations and seeks to develop effective interventions, valid and reliable instruments to measure moral distress are needed. This article describes the development and testing of a revision of the widely used Moral Distress Scale-Revised (MDS-R) to measure moral distress. Methods: We revised the MDS-R by evaluating the combined data from 22 previous studies, assessing 301 write-in items and 209 root causes identified through moral distress consultation, and reviewing 14 recent publications from various professions in which root causes were described. The revised 27-item scale, the Measure of Moral Distress for Healthcare Professionals (MMD-HP), is usable by all HCPs in adult and pediatric critical, acute, or long-term acute care settings. We then assessed the reliability of the MMD-HP and evaluated construct validity via hypothesis testing. The MMD-HP, Hospital Ethical Climate Survey (HECS), and a demographic survey were distributed electronically via Qualtrics to nurses, physicians, and other health care professionals at two academic medical centers over a 3-week period. Results: In total, 653 surveys were included in the final analysis. The MMD-HP demonstrated good reliability. The four hypotheses were supported: (1) MMD-HP scores were higher for nurses (M 112.3, SD 73.2) than for physicians (M 96.3, SD 54.7, p = 0.023). (2) MMD-HP scores were higher for those considering leaving their position (M 168.4, SD 75.8) than for those not considering leaving (M 94.3, SD 61.2, p < 0.001). (3) The MMD-HP was negatively correlated with the HECS (r = -0.55, p < 0.001). (4) An exploratory factor analysis revealed a four-factor structure, reflective of patient, unit, and system levels of moral distress. Conclusions: The MMD-HP represents the most currently understood causes of moral distress. Because the instrument behaves as would be predicted, we recommend that the MMD-HP replace the MDS-R.